Cyanobacteria and cyanotoxins in Polish freshwater bodies. - Kobos, J.; Błaszczyk, A.; Hohlfeld, N.; Toruńska-Sitarz, A.; Krakowiak, A.; Hebel, A.; Sutryk, K; Grabowska, M.; Toporowska, M.; Kokociński, M.; Messyasz, B.; Rybak, A.; et al. (Springer, 2013)
In this work, the authors examined the presence of cyanobacteria and cyanotoxins in 21 samples collected from fresh water bodies located in 5 provinces in Poland: Lublin (2), Podlasie (1), Pomerania (6), Warmia-Masuria (1) and Wielkopolska (11). In addition, to determine the general pattern of geographical distribution, frequency of cyanobacteria occurrence, and cyanotoxins production, the published data from 238 fresh water bodies in Poland were reviewed. On the basis of these collected results, we concluded that Planktothrix, Aphanizomenon, Microcystis and Dolichospermum were dominant. The general pattern in geographical distribution of the identified cyanobacterial genera was typical of other eutrophic waters in Europe. The production of cyanotoxins was revealed in 18 (86%) of the 21 samples analyzed in the present work and in 74 (75%) of the 98 total water bodies for which the presence of toxins had been examined. Among the 24 detected microcystin variants, [Asp3]MC-RR was most common. These results can be verified when more data from the less explored water bodies in the southern and eastern parts of Poland are available.
Keywords: cyanobacterial blooms; cyanotoxins; freshwater cyanobacteria